Autologous Platelet Rich Plasma (PRP) in the treatment of elbow epicondylitis and plantar fasciitis: medium to long term clinical outcome: PRP in P. Fasciitis and epicondylitis - Leigheb, Massimiliano; MASSA, Matteo; BOSETTI, Michela; NICO, Piergiuseppe; TARALLO, Luigi; POGLIACOMI, Francesco; GRASSI, Federico Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Platelet-Rich-Plasma (PRP) is a popular biological therapy especially used to regenerate different musculoskeletal tissues by releasing growth-factors and cytokines promoting cell proliferation, chemotaxis, differentiation, and angiogenesis. The aim was to evaluate the clinical effectiveness and safety of PRP for Lateral-Epicondylitis (LE) of the elbow and Plantar-Fasciitis (PF). Methods: A retrospective study was conducted including patients treated with a single topic autologous-PRP-injection between 1-1-2009 and 7-18-2019 for LE or PF at our institution; patients operated for the same problem, patients refusing the study or not traceable were excluded. Patients were assessed with VAS for pain and clinical scales. Results: 33 patients were treated with PRP and 13 (8F, 5M) included: 4LE and 9PF for a total of 16 cases. The average pain level was 0.61±0.63: 1±1.41 for LE and 0,44±0 for PF. No significant side effect was reported. 4 PRP-treatments failed: 2LE and 2PF. OES and PRTEE gave excellent results for elbow. Average foot scores were AOFAS 98.2±5 and FADI 91.3±1. Patients were stratified and compared according to plantar arch conformation, follow-up length, healing time, time from diagnosis to PRP-treatment, therapies before PRP (physiotherapy, steroid infiltration or shock-waves), risk factors (standing work, sport, age, sex). Conclusions: As in other studies, our results do not allow to draw sufficiently valid conclusions regarding the effectiveness and safety of PRP in the treatment of LE and PF: in particular the statistical significance is limited by the small sample size. PRP can be chosen as a non-first-line treatment for LE and PF.